Explorative Study on Hipertension Treatment among Pregnant Women - Anis Ristyaningsih; Fivy Kurniawati; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Maternal mortality in Indonesia is relatively high, hypertension becomes one of the causes. Hypertension and complication give particular contribution on morbidity and mortality on neonatal and maternal. On the other hand, antihypertensive drug use in  pregnancy has both benefit and risk. Therefore, appropriate hypertension management needs to be assesed in order to minimize the risk in mother and baby. The aim of the study is to determine the utilization pattern of antihypertensive drugs that will be assesed for suitability with the standard of medical service and American College of Obstetrics and Gynecologists (ACOG) guideline, as well as to determine clinical outcome of the therapy, which includes achieving target blood pressure, proteinuria, and edema. This study was a cross-sectional study with retrospective data collected from hospitalized patients’ medical record in RS PKU Muhammadiyah Yogyakarta from 2012 – 2015. The data of patients’ medical records according to inclusion and exclusion criteria was obtained using consecutive sampling method. Data obtained was analyzed descriptively and reviewed with the suitability of standard of medical service and ACOG guideline. Research shows that most widely used antihypertensive drugs are nifedipine by 51,8%, methyldopa by 2,6%, and amlodipine by 2,6%. Based on the evaluation of sensibility of treatment, 75,3% stated right indication, 100% right patient, and right medication and dosage. Clinical outcome includes blood pressure that had achieved the target as many as 77 patient, with negative value of proteinuria and edema. Blood pressure when patients were dismissed from the hospital was on average of 128,9±15,9/85±10,9 mmHg. In general, the utilization pattern of hypertension drugs in pregnant women has been well and according to the standards used.